High visibility first-order subwavelength interference based on light pulse storage via electromagnetically induced transparency - Zhixiang Li (Nature Portfolio, 2017)
Abstract We achieved high visibility first-order subwavelength interference based on light pulse storage and retrieval technique via electromagnetically induced transparency (EIT) effect in a Pr3+:Y2SiO5 crystal. The interference field distribution of a double-slit was first stored in a Pr3+:Y2SiO5 crystal based on EIT effect, and then it was read out by a spatially modulated readout beam. The retrieved output field is proportional to the product of the input interference field of the double-slit and the spatially modulated readout field. High visibility first-order subwavelength interference with an effective wavelength of λ/n, where λ is the wavelength of the input light field and n is any positive integer, can be obtained by designing the spatial modulation structure of the readout field. Experimentally, first-order subwavelength interference with an effective wavelength of λ/3 and a visibility of 67% were demonstrated. Such first-order subwavelength interference has important applications on high resolution optical lithography.